2017
DOI: 10.1037/aca0000141
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the lab: An examination of key factors influencing interaction with ‘real’ and museum-based art.

Abstract: The authors present a comprehensive review and theoretical discussion of factors that could influence our interaction with museum-based art. Art is an important stimulus that reveals core insights about human behavior and thought. Art perception is in fact often considered one of the few uniquely human phenomena whereby we process multiple types of information, experience myriad emotions, make evaluations, and where these elements not only occur but dynamically combine. Art viewing often occurs in museums, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
134
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(154 citation statements)
references
References 142 publications
6
134
0
Order By: Relevance
“…Researchers should consider studying awe in more ecologically valid, real world environments (Anderson, 2016). Like us, others have also shown differences in results from studies done in laboratories vs. museums (Makin, 2017;Pelowski, Forster, Tinio, Scholl & Leder, 2017;Silvia, 2017). Finally, much of the research on emotions in exhibits has shown a greater impact on delayed measures, and recent work on positive impacts of awe on issues such as social well-being and stress has lasted as long as one week after the awe inducing event (Anderson, 2016).…”
Section: Awe and Museum Spaces: Implications For Learningmentioning
confidence: 89%
“…Researchers should consider studying awe in more ecologically valid, real world environments (Anderson, 2016). Like us, others have also shown differences in results from studies done in laboratories vs. museums (Makin, 2017;Pelowski, Forster, Tinio, Scholl & Leder, 2017;Silvia, 2017). Finally, much of the research on emotions in exhibits has shown a greater impact on delayed measures, and recent work on positive impacts of awe on issues such as social well-being and stress has lasted as long as one week after the awe inducing event (Anderson, 2016).…”
Section: Awe and Museum Spaces: Implications For Learningmentioning
confidence: 89%
“…Of course, this is not an easy task, since a myriad of particular characteristics define different contexts and differences between them. In a comprehensive review of the characteristics of museum experience, Pelowski et al (2017) identify three broad groups: (1) features of the artwork; (2) characteristics of the viewer; and (3) characteristics of the presentation context. Features of artworks comprise both physical (size, texture, physical presence, and remnants of the artist's touch and effort) and perceived features (seeing objects as "art" and perceived authenticity).…”
Section: What Causes Difference In Art Experience and Viewing Patternmentioning
confidence: 99%
“…It is well-established that context affects aesthetic experience and that investigations in authentic and ecologically-valid settings such as art museums are important in empirical aesthetics (for a review see Pelowski et al, 2017). Since the seminal work by Locher et al (1999Locher et al ( , 2001, studies in empirical aesthetics conducted in naturalistic settings have proliferated, afforded by new methods and techniques that have become available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, it may be that findings based on small images do not generalize to images in their original size. The issue is discussed extensively in Pelowski, Forster, Tinio, Scholl, and Leder (2017), who argue that lab studies are valuable, but that psychological processes in response to artwork are likely to differ in museum or gallery settings. Specker et al (2017) support this argument with data.…”
Section: Discussionmentioning
confidence: 99%